2015
DOI: 10.1177/0018720815617406
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pulse Oximetry Sonifications for Neonatal Oxygen Saturation Monitoring

Abstract: Adding a beacon to the variable-pitch pulse oximeter sound may help clinicians identify when, and by how much, a neonate's SpO2 deviates from the target range, particularly during patient transport situations when auditory information becomes essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…The rate of the tones represents heart rate and rhythm, and the pitch of the tones represents SpO 2 . Current pulse oximeter sonifications rely on a clinician's ability to perceive relative pitch to infer changes in SpO 2 direction, and their ability to perceive absolute pitch to infer absolute SpO 2 levels . However, although most individuals can easily recognise pitch differences, few can identify absolute pitch .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of the tones represents heart rate and rhythm, and the pitch of the tones represents SpO 2 . Current pulse oximeter sonifications rely on a clinician's ability to perceive relative pitch to infer changes in SpO 2 direction, and their ability to perceive absolute pitch to infer absolute SpO 2 levels . However, although most individuals can easily recognise pitch differences, few can identify absolute pitch .…”
Section: Introductionmentioning
confidence: 99%
“…Commercial pulse oximeters map linear increments of SpO 2 to either fixed or percentage increments in sound frequency (perceived as pitch); the former results in a linear mapping, whereas the latter results in a logarithmic mapping . A logarithmic scale creates approximately equal‐appearing pitch intervals . Under test conditions, clinicians can identify absolute SpO 2 levels more accurately when SpO 2 is mapped to a logarithmic scale than to a linear scale .…”
Section: Introductionmentioning
confidence: 99%
“…1 2 12 Adding further sound properties to attract auditory attention to clinically important thresholds was suggested by Watson and Sanderson 13 and recent laboratory investigations demonstrate the potential of this method for enhancing pulse oximeter sonifications. [4][5][6] However, participants in the recent studies focused solely on the task of SpO 2 monitoring in a quiet environment, and there were no alarms used in the control condition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work we have found that the presence or absence of 11 formal music training can be a sensitive predictor of participants' performance with auditory alarms 9 and sonifications 4 , but such differences become unimportant if all participants perform above some criterion level with a display. In the present experiment we used block randomisation to ensure equal proportions of participants with and without formal music training in each condition.…”
Section: Limitationsmentioning
confidence: 92%
See 1 more Smart Citation